Deficit hídrico na germinação de sementes e crescimento de plântulas de arroz de terras altas - Tirelli, Giovani Virgílio (2021)
Rice is a crop of great global impact, it is the second most consumed cereal and is present daily on the table of more than 2/3 of the entire population. It is a culture that has great importance in the issue of fighting hunger and malnutrition, as it is a food rich in carbohydrates, vitamins and proteins. Brazil is among the ten largest producers, however, the highland variety is far from the potential it has, participating only in ¼ of all national production. Even with this low share in all production, upland rice is of great importance for Brazilian agriculture, it is used to open up and revitalize areas and also has a great influence on price controls in the country. Thus, for more safety in the use of this activity in the country's grain-producing regions, such as the cerrado, the understanding of the environmental effects becomes necessary, especially in the case of drought, since rice farming is one of the most sensitive crops to the lack of water and depending on the dry season, losses can reach 70% of production. The physiological quality of seeds is an important parameter to assess the capacity of a material to form a plant, so its use for selection of more vigorous materials becomes necessary especially when one wants to assess the effect of environmental stresses on different genotypes. Drought is an extreme condition that provides the rice plant with many changes, the antioxidant complex enzymes, for example, are important substances for cell balance, they control the reactive oxygen species, which are free radicals produced naturally in the plant, and prevent their accumulation and possible damage. Knowing that the lack of water promotes changes in plant metabolism, and that through the direct influence on the concentration of CO2 and the overexcitation of photosystem II, there is an increase in the production of reactive oxygen species, the objective of this work was to characterize different upland rice strains regarding the physiological quality and development of seedlings for tolerance to drought incidence and to assess the activity and expression of antioxidant complex enzymes in relation to the response to induction of water stress in the reproductive phase in upland rice genotypes tall.